SME Financing Constraints: Evidence from Survey of Construction Firms in Ghana - Alex Kojo Eyiah; Nongiba Alkanam Kheni; Richard Acquah (International Journal of Small and Medium Enterprises and Business Sustainability, 2018)
Small and medium enterprises (SMEs) play a significant role in a country’s social-economic development. Unfortunately, they are restricted in accessing the capital they require to function effectively in the construction industry. This study investigated the situation from the perspective of contractors operating within the construction industry in Ghana. The quantitative approach to research was adopted using survey questionnaires. With a response rate of 48 percent from 400 questionnaires distributed, the paper gauges the perception of construction firms on the financing constraint and the factors contributing to such constraints. The Chi-Square test was employed to ascertain whether there existed significant differences between the personal and organisational characteristics of firms and financing challenges. The challenges associated with financing of construction firms are multifaceted. To a large extent, the financial class of construction firms was related to their financing constraints. Efforts to mitigate the problem need to be addressed holistically. Perhaps, it is about time consideration is given to establishing a specialised bank for construction. Such a bank would understand the peculiar nature of the construction industry to be able to handle the associated risks. The government, and interested development agencies, has a role to play in ensuring the success of such bank.